LGBTQ Children Narration in Tomboy Movie - Kusumawardhani, Adinda; Dwiningtyas, S.Sos, MA, Dr. Hapsari (Interaksi Online, 2016)
Movie as a form of mass media has the capability to deliver a message to its audiences. Movie become an exact alternative to picture child sexuality. Tomboy is a movie that tries to present child sexuality issue which underrepresented, the story of LGBTQ child living in a conservative neighborhood. So far, LGBTQ child issue considered to be very taboo in society so not much discussed in various domains including movie. The lack of public understanding about LGBTQ child brings out negative speculation about that and finally give an effect of improper handling in the cases of child sexuality. This study aims to describe about LGBTQ children narration in Tomboy movie, using descriptive qualitative method with narrative analysis. This research used, Perspective in Homosexual Theory, Queer Theory, Children Film and Homosexual Theory, Narrative Theory and Film Narrative Analysis. The study found how LGBTQ child narrated in a movie. The findings were compiled in a few points: 1) Child in this movie narrated in the style of storytelling that flows properly as if everyday life with a progressive plot. 2) Child in this movie narrated has LGBTQ tendency (tomboy and lesbian tendency). 3) Child in this movie narrated has LGBTQ tendency because of her own desire not because of another factor. The idea is in line with homosexual theory perspective that claim in some cases, LGBTQ child has discomfort gender roles based on sex as he or she get from birth. 4) Child in this movie narrated performs some efforts and struggle to become a perfect boy. 5) Child in this movie narrated must experience some conflicts because she lives in a conservative neighborhood. 6) Child performativity in this movie does not create a new different gender category, but rather mimics the original which is boy. 7) Child in this movie narrated in the style of art cinema narration. The style provide space for the audience to better appreciate the atmosphere in the ongoing events because the duration of the scene is made longer. And because the style is based on art, the camera technique can be neatly framed the character detail expression and gesture in an event. 8) The power of narration lies in the expression of the main character. Close-up and medium close-up shot types in almost every scene help to potray it.